A Phase I Dose-Finding Study of Silybin Phosphatidylcholine (Milk Thistle) in Patients With Advanced Hepatocellular Carcinoma. (January 2014) - Siegel, Abby B.; Narayan, Rupa; Rodriguez, Rosa; Goyal, Abhishek; Jacobson, DrPH, Judith S.; Kelly, Kara; Ladas, Elena; Lunghofer, Paul J.; Hansen, Ryan J.; Gustafson, Daniel L.; Flaig, Thomas W.; Yann Tsai, Wei; et al.
Purpose . To determine the maximum tolerated dose per day of silybin phosphatidylcholine (Siliphos) in patients with advanced hepatocellular carcinoma (HCC) and hepatic dysfunction. Experimental Design . Patients with advanced HCC not eligible for other therapies based on poor hepatic function were enrolled in a phase I study of silybin phosphatidylcholine. A standard phase I design was used with 4 planned cohorts, dose escalating from 2, 4, 8, to 12 g per day in divided doses for 12 weeks. Results . Three participants enrolled in this single institution trial. All enrolled subjects consumed 2 g per day of study agent in divided doses. Serum concentrations of silibinin and silibinin glucuronide increased within 1 to 3 weeks. In all 3 patients, liver function abnormalities and tumor marker α-fetoprotein progressed, but after day 56 the third patient showed some improvement in liver function abnormalities and inflammatory biomarkers. All 3 participants died within 23 to 69 days of enrolling into the trial, likely from hepatic failure, but it could not be ruled out that deaths were possibly due to the study drug. Conclusion . Short-term administration of silybin phosphatidylcholine in patients with advanced HCC resulted in detectable increases in silibinin and its metabolite, silibinin glucuronide. The maximum tolerated dose could not be established. Since patients died soon after enrollment, this patient population may have been too ill to benefit from an intervention designed to improve liver function tests.